The successful innovations of the affordable care act of 2010 - Ronald D. Hester (Journal of Innovation and Entrepreneurship, 2017)
The purpose of this article is to describe the innovative strategies that were used to develop the first National health insurance program in the United States. The first innovative provisions was the development a fund to expand health coverage under the State Medicaid programs to expand coverage through most Medicaid State Health Plans. The establishment of a new innovative structure of premium subsidies to expand private health insurance for many uninsured Americans, to purchase a Subsidize health plan was the second innovated approach, to finance health insurance to those that were previously uninsured. Unlike most Western nations, that finance health insurance through a national tax or income tax, the American innovative approach relayed on providing government subsidies for individuals to purchase private health insurance plans and/or expand coverage under the existing Medicaid program. This innovated strategy has been very successful to greatly reduce the number of uninsured Americans to be at the lowest since records have been maintained on this topic. However, this program has been successful to lower the number of uninsured Americans, many have opposed this innovated strategy as it relies too much on government subsidies to reduce the number of uninsured. Now efforts are under way to repeal and replace the innovative strategies that have increased the number of insured in the United States.
Keywords: 650; Obamacare; Health Insurance; Tax subsidies; Uninsured Americans